Timeliness Factors of Financial Reports Submission - Tony Sudirgo; Jennifer Krisna Amanda Lo; Gwyneth Margaretha Taniman (International Journal of Application on Economics and Business, 2023)
The purpose of this study is to determine the effect of profitability, leverage, company size, and the size of the public accounting firm on the timeliness of financial report submission. The sampling was done using purposive sampling. The sample used in this study was 61 companies from the property and real estate sector listed on the Indonesia Stock Exchange (IDX) in the period of 2019-2020. This study used a sample of 61 companies for one year, with a total sample of 122 companies for two years. This study uses secondary data taken from the Indonesia Stock Exchange (IDX) and processed using the SPSS 26 data processing application. The analytical methods used are descriptive statistical analysis and logistic regression analysis. The results of data analysis show that profitability, leverage, company size, and the size of the public accounting firm have no significant effect on the timeliness of financial report submission.